Indian Ocean mixed layer depth changes under global warming - Gao, Zhen; Long, Shang-Min; Shi, Jia-Rui; Cheng, Lijing; Li, Gen; Ying, Jun (Frontiers in Climate, 2023)
The surface ocean mixed layer (OML) is critical for climate and biological systems. Changes in ocean mixed layer depth (MLD) of the Indian Ocean under global warming are examined utilizing outputs from 24 climate models in the Coupled Model Intercomparison Project phase 6 (CMIP6) models and the Community Earth System Model 1.0 with Community Atmosphere Model version 5 (CESM1-CAM5). The results show that the MLD generally decreases in low- and high-emissions Shared Socioeconomic Pathway (SSP) scenarios (ssp126 and ssp585). In ssp126 and ssp585, the multi-model ensemble-mean OML respectively shoals about 5% and 10% over both the northern tropics and southern subtropics, with high model consistency. This robust OML shoaling appears in the 1980s and is closely associated with increased surface buoyancy forcing and weakened winds. In contrast, the OML in the south equatorial Indian Ocean slightly deepens and displays large intermodel differences in the sign and magnitude of the changes. The effects of direct CO2 increase and wind changes on OML changes are further quantified by CESM1-CAM5 partially coupled experiments. The results show that the increased surface net heat flux from direct CO2 increase dominates OML shoaling in the northern tropics. In the southern subtropics, the increased surface heat flux, reduced wind speed, and wind-driven divergence all facilitate the OML shoaling. In the south equatorial Indian Ocean, wind changes generally deepen the OML, consistent with the CMIP6 results. Moreover, the OML shoaling-related upper ocean stratification changes are contributed by both temperature and salinity changes in the northern tropics but dominated by temperature changes south of 10°S. These results highlight the regional differences in MLD changes and their forcing, which is important for understanding regional climate changes and corresponding changes in extreme events and biological systems under global warming.